IDENTIFIKASI KESALAHAN PESERTA DIDIK DALAM MEMECAHKAN MASALAH BERDASARKAN NEWMAN’S ERROR ANALYSIS - Zahriah Ilyas (UNZAH Genggong, 2023)
Students need to be trained to be able to solve problems in learning activities, this is done so that they are better prepared to face the challenges of life in the future. An overview of students' abilities in solving physics problems is obtained through appropriate assessments so that students' needs, weaknesses, and mistakes can be identified. This study aims to identify student errors based on Newman's Error Analysis (NEA). The method used is a descriptive method with a quantitative approach and a sample of 20 people who were chosen randomly. The data collection technique used was a test, and the research instrument was in the form of unit conversion test questions in the form of essays in the form of four-item questions. Research data were analyzed using descriptive statistics. The results showed that the percentage of errors for each type of error was 7.50% reading errors, 35% understanding errors, 25% transformation errors, 11.25% processing skills errors, and 7.5% writing errors. Thus it can be concluded that each type of error made by each student is in a low category.